(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes the role and effectiveness of histological (histological) preparations used in the prevention of dystonia. The diagnostic and prophylactic value of these preparations in reducing neuromuscular dysfunctions and detecting pathological changes in the central nervous system at an early stage is highlighted. Also, the possibilities of histological methods in assessing morphological changes in muscle fibers and nerve cells in the pathogenesis of dystonia are considered on a scientific basis. The results of the study serve to improve strategies for the early detection and prevention of dystonia.